PEM hydrogen production membrane electrode with continuously and gradually changed ionomer structure and preparation method of PEM hydrogen production membrane electrode

By adopting the continuous gradient design of the ionomer structure in the catalytic layer of the PEM hydrogen production membrane electrode, the conduction paths of protons and electrons are optimized, the problem of high polarization index of the membrane electrode is solved, the electrolysis performance is improved and the energy consumption is reduced. .

CN119352058APending Publication Date: 2025-01-24BEIJING SMART ENERGY RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411243564.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing PEM hydrogen-making membrane electrodes have high ohmic polarization, activation polarization and mass transfer polarization indicators during the electrolysis process, resulting in high electrolytic energy consumption and poor electrochemical performance, which limits its large-scale commercial application.

Method used

The ionomer structure is designed to continuously change, and by controlling the continuous decrease of the ionomer content in the catalytic layer, from the near-membrane side to the far-membrane side, the conduction path of protons and electrons is optimized and the ohmic impedance is reduced.

Benefits of technology

Efficient construction of proton conduction channels is achieved, ohmic overpotential caused by proton and electron conduction is reduced, electrolysis performance is improved, and energy consumption is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352058A_ABST
    Figure CN119352058A_ABST
Patent Text Reader

Abstract

The invention discloses a PEM hydrogen production membrane electrode and a preparation method thereof. The membrane electrode comprises a proton exchange membrane and a catalyst layer, the catalyst layer comprises a catalyst and an ionomer, and the content of the ionomer is continuously and progressively decreased in the catalyst layer from the near membrane side to the far membrane side. According to the preparation method of the PEM hydrogen production membrane electrode, a proton exchange membrane is coated with a catalyst layer, and the fluidity of an ionomer is regulated and controlled by controlling the drying temperature and the like in the coating process. According to the PEM hydrogen production membrane electrode, an efficient proton conduction channel is constructed, proton conduction is fully improved, meanwhile, the negative influence of ionomers on electron conduction is reduced to the maximum extent, ohmic overpotential caused by proton and electron conduction is integrally reduced, the electrolysis performance is improved, and energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of PEM hydrogen production membrane electrodes, and in particular, the present invention relates to a PEM hydrogen production membrane electrode with a continuously variable ionomer structure and a preparation method thereof. Background Art

[0002] Proton exchange membrane water electrolysis (PEM hydrogen production) technology has the advantages of good adaptability to green electricity fluctuations, high electrolysis efficiency, fast response speed, and low hydrogen-oxygen interpenetration rate. It is a highly promising water electrolysis hydrogen production technology, but the cost and stability of PEM hydrogen production are still the key issues limiting its large-scale commercialization. Reducing electrolysis energy consumption and improving electrochemical performance are currently urgent issues to be solved. Membrane electrode (MEA) is a key component of PEM hydrogen production equipment, which is directly related to the hydrogen production efficiency and cost of electrolysis equipment. The three polarization indicators of the membrane electrode, ohmic polarization, activation polarization, and mass transfer polarization, are crucial to the electrolysis efficiency of the entire electrolyzer. The higher the polarization, the higher the electrolysis overpotential, the higher the energy consumption, and the more unfavorable the hydrogen production efficiency and cost. Therefore, to improve the electrolysis performance of the electrolyzer, it is necessary to reduce the three polarization indicators. The conductivity of the membrane electrode catalyst layer is not only directly related to the ohmic polarization, but also affects the activation polarization. Its structural design needs to consider issues such as improving catalyst utilization, reducing ohmic impedance, and enhancing mass transfer.

[0003] Cost and stability are still the key issues that limit the large-scale commercialization of PEMWE. It is necessary to further optimize the three-phase interface structure of the electrochemical reaction, reduce the energy consumption of electrolysis, improve the electrochemical performance, and reduce the loading of expensive catalysts. The main methods currently adopted are to prepare high-performance catalysts or to improve the effective utilization rate of catalysts by optimizing the design of the membrane electrode (MEA) catalyst layer (CL). At present, most of the catalysts with excellent performance in the three-electrode system have not shown equivalent performance improvement in MEA. Optimizing the structure of the MEA anode catalyst layer to fully utilize the performance of existing catalysts is a simple and effective way to improve water electrolysis performance and reduce catalyst loading.

[0004] Patent application US20120121994A1 discloses a membrane electrode assembly, in which a layer of electrocatalyst particles is embedded in the near-boundary layer of the membrane to obtain a membrane electrode, the membrane electrode having a porosity that allows gas to flow through the electrode, and the surface roughness of the membrane electrode increases the catalytic active area of ​​the electrode, and the roughness and permeability of the metallization layer lead to a thicker electrode, which can lead to a larger catalytic active area and improve water management at the cathode. However, the patent application focuses on the porosity and surface roughness of the membrane electrode, that is, water and gas transmission and activation area, and fails to give full play to the activity of the catalyst.

[0005] Patent application CN117535710A discloses a PEM electrolyzer membrane electrode, which uses a roller with a convex shape to roll the catalyst layer during the preparation process, and controls the protrusion depth of the roller to be <5um, the width to be <50um, and the spacing to be <50um. The cathode catalyst layer and the anode catalyst layer finally obtained have a protruding uniform shape, thereby increasing the contact active area of ​​the cathode catalyst layer and the anode catalyst layer. However, this patent application does not focus on the catalytic activity of the catalyst layer.

[0006] Patent application CN111740122A discloses an ordered membrane electrode, which utilizes the external field driving force of electrochemical deposition to cause the active components to undergo redox reactions on the surface of the gas diffusion layer, so that the catalyst grows in situ on the surface of the gas diffusion layer, thereby obtaining a catalytic layer with a three-dimensional multi-level structure. The catalytic layer with a three-dimensional multi-level structure has a higher active area. This patent application has limited improvement on the ohmic polarization characteristics of the catalytic layer.

[0007] Patent CN106684395B discloses a cathode catalyst layer with gradient porosity and its preparation method. Under the premise of unchanged platinum loading, the catalyst layer pore structure is optimized by controlling the composition of catalyst slurry and the gradient change control of platinum loading during spraying. From the proton exchange membrane side to the gas diffusion layer side, the catalyst layer porosity gradually increases. This catalyst layer with a porosity gradient structure expands the gas / solid / liquid three-phase interface while taking into account the proton conduction capacity. This patent has a gradient porosity structure in the catalyst layer, but the improvement of the polarization characteristics of the membrane electrode is limited.

[0008] It can be seen that there are currently many patents on membrane electrodes, but these patents mainly focus on improving the water vapor transport properties of membrane electrodes or increasing the active area. There are also a small number of porosity gradient structures, and less attention is paid to improving the polarization properties of membrane electrodes. Summary of the invention

[0009] Based on this, the present invention aims to overcome at least one defect of the prior art and provide a PEM hydrogen production membrane electrode with a continuously changing ionomer structure and a preparation method thereof.

[0010] In a first aspect, the present invention relates to a PEM hydrogen production membrane electrode, wherein the membrane electrode comprises a proton exchange membrane and a catalyst layer, wherein the catalyst layer comprises a catalyst and an ionomer, and the ionomer content in the catalyst layer decreases continuously from the proximal side to the distal side of the membrane.

[0011] In a second aspect, the present invention relates to a method for preparing a PEM hydrogen production membrane electrode, wherein a catalyst layer is coated on a proton exchange membrane, wherein the fluidity of the ionomer is regulated by controlling the drying temperature during the coating process, so that the ionomer naturally sinks to a suitable distance during the drying process.

[0012] Therefore, the beneficial effect of the present invention is that the PEM hydrogen production membrane electrode described in the present invention continuously increases the ionomer content from the far membrane side to the near membrane side, thereby constructing an efficient proton conduction channel, and the proton conduction density continuously increases in the near membrane side direction, and at the same time, the electron conduction density continuously increases in the far membrane side direction, which not only fully improves proton conduction, but also minimizes the negative impact of ionomers on electron conduction, reduces the ohmic overpotential caused by proton and electron conduction as a whole, improves electrolysis performance, and reduces energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a schematic diagram of the PEM hydrogen production membrane electrode structure of the present invention. DETAILED DESCRIPTION

[0014] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific implementation methods.

[0015] Regarding the first aspect of the present invention, the catalytic layer where the electrode reaction occurs is a key component of PEM hydrogen production. The microscopic, mesoscopic and macroscopic multi-level structures of the membrane electrode catalyst layer are the key to improving the electrochemical surface area and the effective transmission of protons, electrons, water, product gas and heat. Its structural design needs to consider issues such as improving catalyst utilization, reducing ohmic impedance, and enhancing mass transfer. The catalytic layer is usually composed of a catalyst (providing active sites and electron transmission pathways), an ionomer (providing H+ transmission paths and acting as an adhesive to enhance the mechanical properties of the catalytic layer) and pores (providing transmission paths for reaction water and product gas) to form a continuous cross-network structure, providing a reaction site for the electrochemical reaction. Therefore, the effective catalytic layer network structure not only depends on the catalyst activity, but is also closely related to the accessibility of the active sites to the reaction water, protons and electrons. In the membrane electrode catalyst layer, the ohmic impedance caused by proton conduction has a large space for optimization, which is one of the key considerations in the design of the membrane electrode structure.

[0016] Optimizing the structure of the membrane electrode anode catalyst layer to fully utilize the performance of existing catalysts is a simple and effective way to improve water electrolysis performance and reduce catalyst loading. The construction of the membrane electrode catalyst layer needs to start with the membrane electrode slurry. The morphology of the catalyst-ionomer agglomerates in the membrane electrode slurry and the interconnection form of each component directly affect the three-phase interface of the catalyst layer and the multi-level structure of the catalyst layer. The ohmic impedance of the membrane electrode catalyst layer mainly comes from the proton conduction impedance and the electron conduction impedance. The transmission paths of protons and electrons are opposite. If we focus on reducing the proton conduction impedance by increasing the ionomer content, due to the poor conductivity of the ionomer, this will inevitably lead to an increase in the electron conduction impedance. The continuous variation design of the ionomer content of the present invention fully utilizes the feature that the transmission paths of protons and electrons in the catalyst layer are opposite. The ionomer is increased at the proton transmission density near the membrane side to ensure efficient proton transmission; the ionomer is reduced at the proton conduction density far from the membrane side, which is the high electron conduction density. Therefore, by reducing the ionomer content, the proton conduction requirement is fully guaranteed while the electron conduction requirement is considered.

[0017] like Figure 1 As shown, the PEM hydrogen production membrane electrode of the present invention includes a mass exchange membrane 1, a catalytic layer 2 and a gas transfer layer 3. The present invention controls the structural distribution of the ionomer concentration to continuously decrease from the near-membrane side 4 to the far-membrane side 5, thereby meeting the conduction demand of a higher proton density gradually increasing from the far-membrane side to the near-membrane side, while fully ensuring the demand for electronic conductivity, thereby achieving a further reduction in the ohmic impedance of the membrane electrode, thereby greatly improving the electrochemical performance of the membrane electrode.

[0018] In addition, compared with the existing gradient ionomer structure, although the membrane electrode performance is improved to a certain extent, due to the obvious layered structure of the gradient structure, the reduction of ohmic impedance is limited. Adjusting the ionomer content from a discontinuous gradient structure to a continuous structure can further reduce the ohmic impedance of the membrane electrode, thereby greatly improving the electrochemical performance of the membrane electrode.

[0019] In one preferred embodiment, the catalytic layer includes an anode catalytic layer and a cathode catalytic layer.

[0020] In one preferred embodiment, the continuous decrease is a continuous decrease structure of a non-layered gradient.

[0021] In one preferred embodiment, the mass ratio of the ionomer to the catalyst is 0.05%-20%.

[0022] In one preferred embodiment, the ionomer is a polymer having proton transport capability. Preferably, the ionomer is one or more of a perfluorosulfonic acid polymer, a perfluorocarboxylic acid polymer or a polystyrene sulfonate polymer. The perfluorosulfonic acid polymer is one or more of Formula 1, Formula 2, Formula 3 or Formula 4 as shown below, and the polystyrene sulfonate is sodium polystyrene sulfonate of Formula 5.

[0023]

[0024] In one preferred embodiment, the membrane electrode has a current density of 2A / cm 2 The electrolysis voltage is less than or equal to 1.86V, preferably, the electrolysis voltage is less than or equal to 1.85V, or less than or equal to 1.84V, or less than or equal to 1.83V.

[0025] Regarding the second aspect of the present invention, the existing gradient-designed ionomer structure has a distinct layered structure, which requires the preparation of slurries with different ionomer contents. The more gradient layers there are, the more complicated the preparation process is. The membrane electrode preparation of the present application can obtain the desired continuously changing structure by gradiently reducing the coating temperature. The main idea is that in the process of coating the catalytic layer on the proton exchange membrane, the coating temperature is lowered through programmed control, which will cause the coating to dry more slowly. During the drying process of the slurry, the ionomer therein has a tendency to migrate downward (i.e., toward the proton exchange membrane). In other words, the amount and distance of the downward migration of the ionomer can be controlled by programmed adjustment of the coating temperature, thereby forming a continuous ionomer gradient structure.

[0026] Specifically, temperature programming can be a continuous decrease in one program or a gradual change in multiple programs. Among them, a continuous decrease in one program needs to be combined with the slurry solvent and the coating thickness to achieve the continuous gradual change of the ionomer. In addition, multiple gradual change programs can realize the continuous gradual change structure requirements of the ionomer under various slurry and coating thickness conditions. Because when the next gradient is coated on the catalyst layer of the previous gradual change program, the ionomer can migrate downward as the solvent penetrates downward (i.e., into the catalyst layer of the previous gradient), so that the ionomers on both sides of the interface of the two-level gradient coating no longer present the set gradient content. Since the downward migration of the ionomer can be controlled by controlling the temperature, the ionomer is no longer a gradient structure between the two layers of the interface, but forms a continuous structure with a gradual change in the ionomer content. Because the ionomer is dispersed in the solvent, adjusting the coating temperature can adjust the time for the solvent to dry. After coating, the solvent will flow downward (i.e., in the direction of the proton exchange membrane), and the ionomer will migrate with it in the direction near the membrane side. The drying time can determine the distance and amount of the solvent flowing downward, which can also affect the migration amount and migration distance of the ionomer.

[0027] For the preparation method of PEM hydrogen production membrane electrode, in one preferred embodiment, the coating temperature is programmed to decrease during the coating process, and the programmed gradient level of the coating temperature is ≥1. Preferably, the gradient level can be 1, 2, 3, 4, 5, 6, 7 or more, wherein the coating temperature between each level decreases successively; in addition, each level can be coated with 1 layer, or multiple layers, for example, 2 layers, 3 layers, 4 layers, 5 layers, 10 layers, 20 layers or more layers. When multiple layers are coated at each level, preferably, the coating temperature of each layer is the same or programmed to decrease gradually, and it is only necessary to ensure the formation of a continuous ionomer decreasing structure.

[0028] In one preferred embodiment, the coating temperature ranges from 130°C to 20°C, preferably, the coating temperature ranges from 110°C to 40°C, and more preferably, from 100°C to 50°C.

[0029] In one preferred embodiment, after each layer is coated, the next layer is coated after the coating layer is dried.

[0030] In one preferred embodiment, the coating is at least one of spray coating, blade coating, slot coating, roll-to-roll coating or micro-concave coating.

[0031] In one preferred embodiment, the amount of ionomer added to the slurry used for coating is determined according to the mass ratio of the dry weight of the ionomer to the catalyst, and the mass ratio of the dry weight of the ionomer to the catalyst is 0.05%-20%, for example, it can be 0.1%, 0.5%, 1%, 2%, 5%, 8%, 10%, 12%, 15% or 18%, etc. The amount of ionomer added to the slurry used for each stage of coating can be the same or different, and it is only necessary to ensure that a continuous ionomer decreasing structure is formed.

[0032] Example

[0033] The embodiments of the present invention are only used for illustrative description and should not be construed as limiting the present invention.

[0034] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0035] The above application content of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0036] Unless otherwise specified, the raw materials used in the following examples are common commercially available products.

[0037] Example 1

[0038] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0039] 1) Preparation of slurry: The slurry uses iridium oxide catalyst, the solid content of the slurry is 3 mg / mL, and a mixed solution of water / isopropanol = 3:7 (volume ratio) is used. The mass of the catalyst in the slurry is 0.2783 g, the mass of the solution of 5 wt% of the molecular formula 3 is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0040] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 , coating area is 25cm 2 First, 20 layers are sprayed at 90°C. After the coating is dried, 12 layers are sprayed at 70°C to obtain the membrane electrode.

[0041] Example 2

[0042] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0043] 1) Preparation of slurry: The slurry uses iridium oxide catalyst, the solid content of the slurry is 25 mg / mL, and 100 mL of a mixed solution of water / isopropanol = 2:8 (volume ratio) is used. The mass of the catalyst in the slurry is 2.783 g, and the content of the solution of 5 wt% of the molecular formula 1 is 120 g.

[0044] 2) The membrane electrode was prepared by blade coating, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 , coating area is 100cm 2 First, apply a layer at 85°C, and after it dries, continue to apply a second layer at 60°C on the coating to obtain the required membrane electrode.

[0045] Example 3

[0046] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0047] 1) Preparation of slurry: The slurry uses iridium oxide catalyst, the solid content of the slurry is 3 mg / mL, and a mixed solution of water / isopropanol = 3:7 (volume ratio) is used. The catalyst mass in the slurry is 0.2783 g, the content of 5wt% sodium polystyrene sulfonate (molecular formula is Formula 5) is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0048] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 , coating area is 25cm 2 First, spray 10 layers at 90°C; after the coating is dry, spray 10 layers at 70°C; after the coating is dry, spray 12 layers at 60°C to obtain the required membrane electrode.

[0049] Example 4

[0050] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0051] 1) Preparation of slurry: The slurry uses iridium oxide catalyst, the solid content of the slurry is 3 mg / mL, and a mixed solution of water / isopropanol = 3:7 (volume ratio) is used. The mass of the catalyst in the slurry is 0.2783 g, the content of the 5 wt% solution of the formula 2 is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0052] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 2 mg / cm 2 , coating area is 25cm 2 , spray 5 layers at 90°C, spray 12 layers at 85°C, spray 10 layers at 75°C, and spray 5 layers at 65°C in sequence to obtain the required membrane electrode.

[0053] Example 5

[0054] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0055] 1) Preparation of slurry: The solvent composition is a mixed solution of water / isopropanol = 2:8 (volume ratio), the solid content of the slurry is 20 mg / mL, the catalyst mass of iridium oxide content is 27.83 g, and the solution content of 5 wt% of the formula 4 is 120 g.

[0056] 2) The membrane electrode was prepared by slit coating, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 2 mg / cm 2 , coating area is 100cm 2First, apply one layer at 90°C, and after it dries, apply the second layer at 65°C on top of the coating.

[0057] Comparative Example 1

[0058] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0059] 1) Preparation of slurry: The solid content of the slurry is 3 mg / mL, and the solvent composition is a mixed solution of water / isopropanol = 3:7 (volume ratio). The mass of the iridium oxide catalyst in the slurry is 0.2783 g, the content of the 5 wt% solution of the formula 2 is 0.48 g, and the total volume of water and isopropanol is 93 mL.

[0060] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 , coating area is 25cm 2 , spray 32 layers at 90℃ to obtain the membrane electrode.

[0061] Comparative Example 2

[0062] A PEM hydrogen production membrane electrode, the preparation process of which is as follows:

[0063] 1) Prepare 2 slurries, No. 1 slurry: using iridium oxide catalyst, the solid content of the slurry is 3 mg / mL, the solvent composition is a mixed solution of water / isopropanol = 3:7 (volume ratio). The catalyst mass in the slurry is 0.2783g, the content of 5wt% nafion is 0.48g, and the total volume of water and isopropanol is 93mL. No. 2 slurry: the solution content of formula 2 is 0.96g, and the rest is the same as No. 1 slurry.

[0064] 2) The membrane electrode was prepared by ultrasonic atomization spraying, using a 127 μm thick perfluorosulfonic acid resin membrane and a catalyst loading of 1.3 mg / cm 2 , coating area is 25cm 2 First, spray 20 layers of slurry No. 1 at 90°C. After the coating is dried, spray 12 layers of slurry No. 2 at 90°C to obtain the required membrane electrode.

[0065] The membrane electrode described in Examples 1 to 5 and Comparative Examples 1 and 2 was subjected to a performance test. The membrane electrode electrolysis performance test was performed using a single cell fixture at a current density of 2 A / cm 2 , the reaction temperature is 50°C, and the test results are shown in Table 1.

[0066] Table 1

[0067]

[0068] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A PEM hydrogen production membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane and a catalyst layer, wherein the catalyst layer comprises a catalyst and an ionomer, and the ionomer content in the catalyst layer decreases continuously from the proximal side of the membrane to the distal side of the membrane.

2. The PEM hydrogen production membrane electrode according to claim 1, characterized in that: The continuous decrease is a continuous decrease structure of a non-layered gradient.

3. The PEM hydrogen production membrane electrode according to claim 2, characterized in that: The mass ratio of the ionomer to the catalyst is 0.05%-20%.

4. The PEM hydrogen production membrane electrode according to any one of claims 1 to 3, characterized in that: The ionomer is a polymer having proton transport capability.

5. The PEM hydrogen production membrane electrode according to any one of claims 1 to 3, characterized in that: The ionomer is one or more of a perfluorosulfonic acid polymer, a perfluorocarboxylic acid polymer or a polystyrene sulfonate polymer.

6. The PEM hydrogen production membrane electrode according to claim 5, characterized in that: The perfluorosulfonic acid polymer is one or more of Formula 1, Formula 2, Formula 3 or Formula 4, and the polystyrene sulfonate is sodium polystyrene sulfonate of Formula 5. The membrane electrode is at a current density of 2A / cm 2 The electrolysis voltage is less than or equal to 1.86V.

7. A method for preparing a PEM hydrogen production membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane and a catalyst layer, wherein the catalyst layer comprises a catalyst and an ionomer, and the ionomer content in the catalyst layer decreases continuously from the proximal membrane side to the distal membrane side. The preparation method comprises the following steps: A catalyst layer is coated on the proton exchange membrane, wherein the fluidity of the ionomer is regulated by controlling the drying temperature during the coating process, so that the ionomer naturally sinks to a suitable distance during the drying process.

8. The preparation method according to claim 7, characterized in that: The coating temperature is programmed to decrease during the coating process; and / or the coating temperature ranges from 130°C to 20°C.

9. The preparation method according to claim 7, characterized in that: And / or, the coating is at least one of spray coating, blade coating, slit coating, roll-to-roll coating or micro-concave coating.

10. The method for preparing a PEM hydrogen production membrane electrode according to claim 7, characterized in that: In the slurry used for coating, the amount of the ionomer added is determined according to the mass ratio of the ionomer dry weight to the catalyst, and the mass ratio of the ionomer dry weight to the catalyst is 0.05%-20%.

Citation Information

Patent Citations

  • Manufacturing process of cathode catalyst layer with gradient porosity for fuel cells

    CN106684395B

  • Ordered membrane electrode and preparation method thereof

    CN111740122A

  • PEM electrolytic cell membrane electrode and preparation method thereof

    CN117535710A

  • Membrane And Catalyst Composite For Membrane Electrode Assembly

    US20120121994A1